1999
DOI: 10.1021/jp982341t
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Deposition of W(VI) Species and Ni(II) Ions on the γ-Alumina Surface:  Mechanistic Model

Abstract: The simultaneous deposition (co-deposition) of W(VI) species and Ni(II) ions on the γ-alumina surface, from aqueous solutions using "equilibrium deposition followed by filtration" (EDF), has been studied in the pH range 4.2-6.2. It was found that the deposition of W(VI) species and Ni(II) ions on the γ-alumina surface in the presence of Ni(II) ions and W(VI) species, respectively, takes place mainly through adsorption of W x O y zor Ni 2+ ions on energetically equivalent sites at the inner Helmhotz plane (IHP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…A better insight at a molecular level may be obtained through the models proposed for the description of the structure of the electrical double layer (edl) at the HAP/water interface. The triple layer model has been proven to successfully describe interfacial phenomena at the oxide/water interface . The application of this model to the HAP/water interface suggested that the adsorbed negatively charged species of phospho- l -serine (HL 2- ) should be located either at the inner Helmholtz plane (IHP) or in the diffuse part at the double layer.…”
Section: Resultsmentioning
confidence: 99%
“…A better insight at a molecular level may be obtained through the models proposed for the description of the structure of the electrical double layer (edl) at the HAP/water interface. The triple layer model has been proven to successfully describe interfacial phenomena at the oxide/water interface . The application of this model to the HAP/water interface suggested that the adsorbed negatively charged species of phospho- l -serine (HL 2- ) should be located either at the inner Helmholtz plane (IHP) or in the diffuse part at the double layer.…”
Section: Resultsmentioning
confidence: 99%
“…As proposed in the Introduction, the Pb 2+ stabilizer affects the plating rate ( R ) and phosphorus content (P%) in the deposition layer (Ni−P alloy) via the electronic effect. The electron effect means the fluctuation of electron flow density occurring in the S−G EDL (Figure ), wherein the IHP is attached by anions (e.g., H 2 PO 2 - , H 2 PO 3 - , and SO 4 2- ) except water molecules and the OHP mainly by solvated cations (e.g., Ni 2+ , Na + , etc.). On the basis of this model, Ni 2+ ions pick up electrons and are converted to metal atoms within the EDL.…”
Section: Structural Relevancy For Electron Transfer In the Stern-grah...mentioning
confidence: 99%
“…[17][18][19] It is a well-established fact that W cannot be deposited in a pure state from aqueous solutions; however, W element can be co-deposited with iron-group metals, resulting in the iron-group alloys. [20][21][22][23] This phenomenon is called "induced co-deposition". The deposition mechanism of induced co-deposition (such as Co-W) is illustrated as the following scheme:…”
Section: Introductionmentioning
confidence: 99%